Effect of combined application of plant defense-inducing chemical, inorganic salt and hot water treatment for the management of postharvest anthracnose of banana (Colletotrichum musae) - Fetiha Seid; Kumlachew Alemu; Binyam Tsedaley (Discover Food)
Abstract Postharvest anthracnose of bananas, caused by Colletotrichum musae, is the most serious disease affecting banana production and consumption globally. The aim of the study was to determine the effect of integrated preharvest application of Plant Defense-Inducing Chemicals (PDIC), namely salicylic acid, jasmonic acid, and Potassium phosphate, along with postharvest salt and hot water treatment for the management of postharvest banana anthracnose disease. Findings of our research showed that integrated application of PDIC before harvest and treatment of fruit with salt and hot water after harvest significantly (p < 0.05) decreased the intensity of anthracnose disease in artificially inoculated banana fruit. Two weeks after inoculation, anthracnose incidence in the untreated control fruit reached 100%; however, preharvest applications of salicylic acid combined with CaCl2 and hot water at 51 °C significantly decreased this level to 20%. Moreover, the application of salicylic acid + CaCl2 + hot water at 51 °C, and Jasmonic acid + CaCl2 + hot water at 51 °C, were effective in reducing disease severity to below 1.6, compared to the untreated control, which showed a severity scale of 4.4. This combination of the treatments significantly increases the marketability of banana fruit to 86.67 and 80.00%, respectively. In conclusion, applications of salicylic acid and jasmonic acid with CaCl2 and hot water at 51 °C were effective in suppressing disease development and improving the marketability of banana without a noticeable effect on their edible qualities. Graphical Abstract